2015
DOI: 10.1007/8904_2015_446
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Catastrophic Presentation of X-Linked Adrenoleukodystrophy

Abstract: Objective: We report a novel presentation of childhood cerebral X-linked adrenoleukodystrophy: status epilepticus followed by abrupt and catastrophic neurologic deterioration.Methods: A description of the clinical presentation, laboratory evaluation, and imaging findings leading to a diagnosis of X-linked adrenoleukodystrophy.Results: A 3-year-old male with prior history of autism presented with fever, diarrhea, and status epilepticus requiring a pentobarbital coma. Admission labs were notable only for a gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…2 ). These data bolster our view that: (1) environmental stress in the form of seizure triggered neurodegeneration in a leukodystrophy patient with a predisposing ACS mutation ( Sivachenko et al, 2016 ), and (2) traumatic brain injury triggered neurodegeneration in patients with catastrophic presentations of ALD ( Raymond et al, 2010 ; Vawter-Lee et al, 2015 ; Weller et al, 1992 ). Moreover, as stress might precipitate a degenerative cellular phenotype when product generation is required to repair damaged or depleted cellular components, our bgm/dbb stress studies suggest that esterified LCFA and VLCFA products of Bgm and Dbb activity are required to prevent neurodegeneration, a hypothesis that contradicts the long-held view that precursor accumulation is causative of neurodegeneration in ALD patients.…”
Section: Discussionsupporting
confidence: 70%
“…2 ). These data bolster our view that: (1) environmental stress in the form of seizure triggered neurodegeneration in a leukodystrophy patient with a predisposing ACS mutation ( Sivachenko et al, 2016 ), and (2) traumatic brain injury triggered neurodegeneration in patients with catastrophic presentations of ALD ( Raymond et al, 2010 ; Vawter-Lee et al, 2015 ; Weller et al, 1992 ). Moreover, as stress might precipitate a degenerative cellular phenotype when product generation is required to repair damaged or depleted cellular components, our bgm/dbb stress studies suggest that esterified LCFA and VLCFA products of Bgm and Dbb activity are required to prevent neurodegeneration, a hypothesis that contradicts the long-held view that precursor accumulation is causative of neurodegeneration in ALD patients.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, in addition to revealing severe neurological involvement, activity phenotypes can be monitored in higher-throughput assays, and this opportunity underscores the feasibility of suppression screens for the identification of compounds and/or dietary regimens that alleviate the abnormalities associated with ACS mutation. Finally, highlighting the continuing power of simple invertebrate genetic models, this study has led to our recognition of a new candidate susceptibility gene for catastrophic presentation of leukodystrophy ( Vawter-Lee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 95%
“…Comparative genotype/phenotype data, coupled with our observation that treatment of the proband with levetiracetam to control seizures unexpectedly stemmed the progression of his neurodegenerative condition, leads us to speculate that, in this patient, seizures are the trigger of a neurodegenerative condition linked to a susceptibility locus, with SLC27a6 being a likely candidate. There is ample evidence for other ALD cases where events such as epileptic seizure or traumatic brain injury have been proposed to precipitate onset of leukodystrophy symptoms in previously asymptomatic individuals ( Weller et al, 1992 ; Raymond et al, 2010 ; Vawter-Lee et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory demyelinating lesion appears to begin at the same site as the original contusion. 5,43,44 Musolino et al reported that an increase in BBB permeability precedes inflammatory demyelination, suggesting that disruption of the BBB may trigger pro-inflammatory demyelination in ALD. 45 It is thus possible that head trauma triggers the inflammatory cerebral ALD presumably due to the BBB disruption.…”
Section: Discussionmentioning
confidence: 99%